Characterization of enamel caries lesions in rat molars using synchrotron X‐ray microtomography. (18th August 2017) - Free, R. D.; DeRocher, K.; Stock, S. R.; Keane, D.; Scott-Anne, K.; Bowen, W. H.; Joester, D.
Abstract : Synchrotron X‐ray microtomography non‐destructively maps demineralization within carious rat molar enamel. Depth profile analysis and lesion characterization reveals that many rat carious lesions possess intact surface zones that are similar in form but much thinner than those found in human caries. Abstract : Dental caries is a ubiquitous infectious disease with a nearly 100% lifetime prevalence. Rodent caries models are widely used to investigate the etiology, progression and potential prevention or treatment of the disease. To explore the suitability of these models for deeper investigations of intact surface zones during enamel caries, the structures of early‐stage carious lesions in rats were characterized and compared with previous reports on white spot enamel lesions in humans. Synchrotron X‐ray microcomputed tomography non‐destructively mapped demineralization in carious rat molar specimens across a range of caries severity, identifying 52 lesions across the 30 teeth imaged. Of these lesions, 13 were shown to have intact surface zones. Depth profiles of fractional mineral density were qualitatively similar to lesions in human teeth. However, the thickness of the surface zone in the rat model ranges from 10 to 58 µm, and is therefore significantly thinner than in human enamel. These results indicate that a fraction of lesions in rat caries possess an intact surface zone and are qualitatively similar to human lesions at the micrometer scale. This suggests that rat caries models may be a suitable analog through which to investigate the structure of surface zone enamel and its role during dental caries.